Description of Injury Patterns in Traffic Accident Victims of Motorcyclist in the Emergency Room TK. II 03.05.01 Dustira Hospital Cimahi Year 2021-2022 - Andri Andrian Rusman; Ilma Fiddiyanti; Yuda Pratama (Jurnal EduHealth, 2025)
Traffic accidents among motorcyclists are a problem that causes many fatalities. Based on the Central Statistics Agency (BPS), in 2021 the number of motorbikes in Indonesia reached 120 million, which increases every year. According to WHO, every year around 20 to 50 million people experience accidents and 1.3 million of them die. The high mortality rate is caused by many things, such as the low level of compliance of drivers with the rules and the slow handling of traffic accident cases to existing emergency facilities. The aim of this research was to determine the pattern of injuries of motorbike traffic accident victims in the emergency room II 03.05.01 Dustira hospital Cimahi 2021-2022. This type of research is retrospective descriptive by looking at medical record data of ER patients at the II 03.05.01 Dustira hospital Cimahi in 2021- 2022. The results of this research obtained 100 medical record data in 2021-2022. Victims were predominantly aged 15-29 years, 53 victims (53%), male, 79 victims (79%), location The wounds were in the upper extremities in 38 cases (33.3%), the majority of victims' wound patterns were abrasions in 49 cases (40.2%) and the radiological images obtained were predominantly fractures in 17 cases (17%). Based on the literature, the most common location is the head, the conclusion of this study is that the upper extremities are the main support when riding a motorbike with the majority of victims are men aged 15-29 years.